2016
DOI: 10.1371/journal.pone.0146119
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Variations in Retention in Care among HIV-Infected Adults in the United States

Abstract: ObjectiveTo understand geographic variations in clinical retention, a central component of the HIV care continuum and key to improving individual- and population-level HIV outcomes.DesignWe evaluated retention by US region in a retrospective observational study.MethodsAdults receiving care from 2000–2010 in 12 clinical cohorts of the North American AIDS Cohort Collaboration on Research and Design (NA-ACCORD) contributed data. Individuals were assigned to Centers for Disease Control and Prevention (CDC)-defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 56 publications
2
28
1
2
Order By: Relevance
“…This is consistent with studies that have shown demographic and geographic variation in HIV clinical outcomes. 33,37,38 …”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with studies that have shown demographic and geographic variation in HIV clinical outcomes. 33,37,38 …”
Section: Discussionmentioning
confidence: 99%
“…For example, research has shown that physicians often defer ART initiation for some PWID because of concerns of a so-called unstable lifestyle and competing priorities that could lead to noncompliance, and potentially the emergence and transmission of drug-resistant HIV [38]. Such concerns have subsequently contributed to lower levels of access to treatment among HIV-positive PWID [42], thus contributing to higher mortality rates in this group.…”
Section: Hiv/aids-related Mortality In the Modern Treatment Eramentioning
confidence: 99%
“…Substantial geographical disparities in HIV care continuum indicators such as diagnosis, linkage, and treatment exists within the United States (US) [2, 3] . For instance, the average lifetime risk of HIV diagnosis for a US adult is 1% (i.e., 1/99), yet the risk is as high as 7.8 % (i.e., 1/13) for individuals in Washington D.C and as low as 0.14% (i.e., 1/670) for individuals in North Dakota [4] .…”
Section: Introductionmentioning
confidence: 99%